RNA interference of a trehalose-6-phosphate synthase gene reveals its roles during larval-pupal metamorphosis in Bactrocera minax (Diptera: Tephritidae). (August 2016) - Xiong, Ke-Cai; Wang, Jia; Li, Jia-Hao; Deng, Yu-Qing; Pu, Po; Fan, Huan; Liu, Ying-Hong
Graphical abstract: Highlights: A trehalose-6-phosphate synthase gene BmTPS was cloned from Bactrocera minax . The expression of four genes in the chitin biosynthesis pathway was induced by 20E. Silencing of BmTPS exhibited 52% death and abnormal phenotypes. RNAi of TPS influences the trehalose/glucose balance in the insects. Demonstrating the feasibility of RNAi in B. minax for the first time. Abstract: Trehalose is the major blood sugar in insects, which plays a crucial role as an instant source of energy and the starting substrate for chitin biosynthesis. In insects, trehalose is synthesized by catalysis of an important enzyme, trehalose-6-phosphate synthase (TPS). In the present study, a trehalose-6-phosphate synthase gene from Bactrocera minax ( BmTPS ) was cloned and characterized. BmTPS contained an open reading frame of 2445 nucleotides encoding a protein of 814 amino acids with a predicted molecular weight of 92.05 kDa. BmTPS was detectable in all developmental stages of Bactrocera minax and expressed higher in the final- (third-) instar larvae. Tissue-specific expression patterns of BmTPS showed that it was mainly expressed in the fat body. The 20-hydroxyecdysone (20E) induced the expression of BmTPS and three genes in the chitin biosynthesis pathway. Moreover, injection of double-stranded RNA into third-instar larvae successfully silenced the transcription of BmTPS in B. minax, and thereby decreased the activity of TPS and trehalose content. Additionally, silencing of BmTPS inhibited the expression of three key genes in the chitin biosynthesis pathway and exhibited 52% death and abnormal phenotypes. The findings demonstrate that BmTPS is indispensable for larval-pupal metamorphosis. Besides, the establishment of RNAi experimental system in B. minax would lay a solid foundation for further investigation of molecular biology and physiology of this pest.